Clinicopathological characteristics of idiopathic membranous nephropathy in 65 elderly patients - LIU Wen-xue; DONG Yuan-zheng; YANG Huan-rong (Linchuang shenzangbing zazhi)
Objective To investigate the clinical and pathological features of idiopathic membranous nephropathy(IMN) in the elderly,to guide the clinical treatment and prognosis of the disease.Methods The clinical and pathological features of 107 patients with IMN who diagnosed in our hospital,65 elderly patients and 42 young patients,were retrospectively analyzed.Results IMN with nephrotic syndrome(NS) as the main clinical manifestations,to edema as the main symptom,the occurrence rate of chronic renal failure,infection,thrombosis,etc.complications and the levels of blood glucose,blood pressure,heart failure index,serum creatinine triglyceride,cholesterol,phospholipase A2 receptourine antibodies,β2-microglobulin were higher in elderly patients than that in young group(P<0.05),but the level of estimated glomerular filtration rate was significantly lower than that of the young group(P<0,05).however there was no statistically significant difference of blood urea nitrogen、hemoglobin、albumin、prothrombin time、urine protein quantitative and urine NAG enzyme(P>0.05).The mainl pathology of IMN patients was Ⅰ and Ⅱ stage.Mesangial cell proliferation,interstitial fibrosis,inflammatory cell infiltration,renal tubular atrophy,and the degree of vascular sclerosis in the elderly were significantly more than that in the young group(P<0.05).The deposition of IgG and complement C3 in the two groups was significantly higher than that of IgA,IgM and complement C4,Clq,but there was no statistically significant difference between the groups(two groups of PLA2 R sediment concentration has significant difference(P<0.01).The renal pathologic injury with IMN patients has positive correlation with the level of BP,SCr,BS,TCHO,TG,PLA2 R,Upro,β2-MG and negative correlation with the level of Alb,eGFR.Conclusions Elderly patients with IMN with nephrotic syndrome(NS) as the main clinical manifestations,edema as the main symptom,pathological stage Ⅰ and Ⅱ,the proliferation of mesangial cells,fibrosis,inflammatory cell infiltration,tubular atrophy and interstitial fibrosis,renal vascular sclerosis heavier,complication rate is high.